Frequency Response Analysis for Three-Phase Star and Delta Induction Motors: Pattern Recognition and Fault Analysis Using Statistical Indicators - Salem Mgammal Al-Ameri, Salem Mgammal Al-Ameri; Zulkurnain Abdul-Malek, Zulkurnain Abdul-Malek; Ali Ahmed Salem, Ali Ahmed Salem; Zulkarnain Ahmad Noorden, Zulkarnain Ahmad Noorden; Ahmed Allawy Alawady, Ahmed Allawy Alawady; Mohd Yousof, Mohd Fairouz; Mohamed Ibrahim Mosaad, Mohamed Ibrahim Mosaad; Ahmed Abu-Siada, Ahmed Abu-Siada; Hammam Abdurabu Thabit, Hammam Abdurabu Thabit (Mdpi, 2023)
This paper presents a new investigation to detect various faults within the three-phase star and delta induction motors (IMs) using a frequency response analysis (FRA). In this regard, experimental measurements using FRA are performed on three IMs of ratings 1 HP, 3 HP and 5.5 HP in normal conditions, short-circuit fault (SC) and open-circuit fault (OC) conditions. The SC and OC faults are applied artificially between the turns (Turn-to-Turn), between the coils (Coil-to-Coil) and between the phases (Phase-to-Phase). The obtained measurements show that the star and delta IMs result in dissimilar FRA signatures for the normal and faulty windings. Various statistical indicators are used to quantify the deviations between the normal and faulty FRA signatures. The calculation is performed in three frequency ranges: low, middle and high ones, as the winding parameters including resistive, inductive and capacitive components dominate the frequency characteristics at different frequency ranges. Consequently, it is proposed that the boundaries for the used indicators facilitate fault identification and quantification.